2023
DOI: 10.3390/su151814013
|View full text |Cite
|
Sign up to set email alerts
|

Foreign Direct Investment, Technological Innovations, Energy Use, Economic Growth, and Environmental Sustainability Nexus: New Perspectives in BRICS Economies

Abdul Rauf,
Najabat Ali,
Muhammad Nauman Sadiq
et al.

Abstract: In the current era, economic growth is inevitable for global prosperity but achieving sustainable economic development is one of the significant challenges for the developing world. The present study explores the impacts of foreign direct investment, energy use, and technological innovations on the economic growth and environmental quality of BRICS countries for the period 1990–2018. We used the augmented mean group (AMG), the common correlated effects mean group estimator (CCEMG), and several other modern-day… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 18 publications
(3 citation statements)
references
References 91 publications
0
3
0
Order By: Relevance
“…This research indicates that inward foreign direct investments, an increase in trade openness, economic growth, and commitment of more money to research all lead to an increase in innovations. Rauf et al (2023) investigated how foreign direct investment, energy use, and technical innovations affected BRICS countries' economic growth and quality of the environment in 1990 and 2018. This suggests that FDI positively impacts growth but impairs sustainability, while innovation technology improves sustainability.…”
Section: Empirical Evidencementioning
confidence: 99%
“…This research indicates that inward foreign direct investments, an increase in trade openness, economic growth, and commitment of more money to research all lead to an increase in innovations. Rauf et al (2023) investigated how foreign direct investment, energy use, and technical innovations affected BRICS countries' economic growth and quality of the environment in 1990 and 2018. This suggests that FDI positively impacts growth but impairs sustainability, while innovation technology improves sustainability.…”
Section: Empirical Evidencementioning
confidence: 99%
“…Innovation catalyzes economic growth by fostering productivity enhancements, technological advancements, and market expansion [1][2][3][4]. Through the development of new products, services, and processes, innovation drives efficiency gains, increasing output and contributing to overall economic expansion [5][6][7][8].…”
Section: Introductionmentioning
confidence: 99%
“…Ali et al (2021) argued that in the long run, if decision-makers do not take adequate and timely measures, emergencies could negatively impact the environment. Rauf et al (2023) suggest that governments should adopt environmentally sustainable economic policies to reduce carbon emissions while attracting environmental protection technologies and encouraging investment in renewable energy projects to enhance regional environmental quality. Ali et al (2022) found that green innovation aids BRICS countries in achieving their goal of environmental sustainability.…”
Section: Introductionmentioning
confidence: 99%